1991
DOI: 10.1007/bf00011903
|View full text |Cite
|
Sign up to set email alerts
|

Role of bacterial cyanide production in differential reaction of plant cultivars to deleterious rhizosphere pseudomonads

Abstract: Lettuce and wheat cultivars, differing in reaction to root inoculation with plant growth-inhibitory bacteria, were tested for sensitivity to (i) gaseous metabolites produced by deleterious, cyanogenic isolates of Pseudomonasfluorescens, and to (ii) pure cyanide. Reactions were read as shoot and/or root elongation after exposure of seedlings to the volatiles in vitro. Lettuce cultivar Salad Bowl was significantly less sensitive than cv. Montana, both to bacterial volatiles and to pure cyanide, and a similar dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 32 publications
(21 reference statements)
0
0
1
1
Order By: Relevance
“…Cyanide production is virtually the only proposed mechanism with enough supporting data [40, 41], whereas other studies have suggested the benefit of hydrogen cyanide based on antifungal activity [42]. The current study did not show a significant correlation between cyanide production and plant growth.…”
Section: Discussioncontrasting
confidence: 46%
“…Cyanide production is virtually the only proposed mechanism with enough supporting data [40, 41], whereas other studies have suggested the benefit of hydrogen cyanide based on antifungal activity [42]. The current study did not show a significant correlation between cyanide production and plant growth.…”
Section: Discussioncontrasting
confidence: 46%
“…Είναι πιθανό η παραγωγή του υδροκυανίου να έχει διαφορετική επίδραση ανάλογα με τον ξενιστή. Για τα φυτά καπνού για παράδειγμα, η επίδραση είναι εμφανώς θετική (Voisard et al, 1989) ενώ όπως προαναφέρθηκε, σε φυτά πατάτας, μαρουλιού και φασολιάς, η αύξηση φαίνεται ότι αναστέλλεται (Bakker & Schippers, 1987;Bakker et al, 1989;Åström & Burns, 1989).…”
Section: συζήτησηunclassified